Effect of Ti on the corrosion behaviour of as-cast Fe–17Cr ferritic stainless steel. (3rd April 2021) - Fu, Junwei; Cui, Kai; Li, Feng; Wu, Yucheng
ABSTRACT: The effect of Ti addition on the microstructure and corrosion resistance of the as-cast Ti-stabilised Fe–17Cr ferritic stainless steels was investigated by optical microscopy, scanning electron microscopy, X-ray diffraction and energy-dispersive spectrometer. The corrosion behaviour of the as-cast Fe–17Cr ferritic stainless steel in 10 wt-% HNO3 and 10 wt-% NaOH solutions was examined by using potentiodynamic polarisation curves and electrochemical impedance spectroscopy. After Ti addition from 0.06 to 0.26 wt-%, the size of TiN precipitates in the as-cast Fe–17Cr ferritic stainless steel increases and the corrosion resistance is improved in 10 wt-% HNO3 and 10 wt-% NaOH solutions, especially in 10 wt-% HNO3 solution. Mott–Schottky curves demonstrate that the addition of Ti can inhibit the decomposition of the passive film, which can improve corrosion resistance.